Geochemical characterization of mineral prospects and Paccha Huamanya Lagunas, Ancash - Peru - Cornelio Orbegoso, Félix (2012)
The mining project comprises Inca mining prospects and Huamanya Paccha Lagunas, located in the Ancash Peru Mining Company SA Mining Prospect Laguna Paccha be defined as a porphyry molybdenum-copper hosted in porphyritic dacite hipabisal of cutting sedimentary units, alteration type is potassium (orthoclase + biotite + quartz) with mineralization generated by strong to moderate millimetric to centimetric quartz containing fine aggregates sulfides in veinlets peripheral to porphyry system will have the presence of mesothermal quartz veins + sulfide + gold. The geochemical distribution has a core with the W-Mo-Re association, surrounded by the Cu-Mo-Re association, the latter has on its periphery a halo with the Pb-Zn elements, this zonation of elements can be generated by differentiation Like in the porphyry. The mining prospect Huamanya Laguna consists of a system of veins of quartz + sulfide + gold mesothermal type. The host rock corresponds to a tonalite intrusive, which presents a hydrothermal alteration of an argillic type filítico superimposition. Mineralization as an economic mineral gold which is mainly associated with arsenopyrite. The geochemical distribution of the elements in the mesothermal veins intrusive zoning has an internal core with the W-Cu association and an outer core with Cu-Mo-Re. The Au-Ag-Bi-Sb-As association presents its highest values ​​around the outcrops.